6(x+1)^2+2(x-1)(x^2+x+1)-2(x+1)^3=32 tìm x

Question

6(x+1)^2+2(x-1)(x^2+x+1)-2(x+1)^3=32 tìm x

in progress 0
Farah 9 months 2020-11-01T15:52:29+00:00 1 Answers 79 views 0

Answers ( )

    0
    2020-11-01T15:53:47+00:00

    Đáp án:

     $x=5$

    Giải thích các bước giải:

    $6.(x+1)^2+2.(x-1).(x^2+x+1)-2.(x+1)^3=32$

    $⇔6.(x^2+2x+1)+2.(x^3-1)-2.(x^3+3x^2+3x+1)=32$

    $⇔6x^2+12x+6+2x^3-2-2x^3-6x^2-6x-2=32$

    $⇔6x+2=32$

    $⇔6x=30$

    $⇔x=5$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )